A proposed seasonal cycle of dissolved iron-binding ligands in Antarctic sea ice - Genovese, C; Grotti, M; Ardini, F; Matthew Corkill; Duprat, LP; Kathrin Wuttig; Ashley Townsend; Delphine Lannuzel (2022)
Iron (Fe) is an essential micronutrient to oceanic microalgae, and its dissolved fraction (DFe) is retained in surface waters by Fe-binding ligands. Previous work has suggested that ligands may also bind Fe within sea ice, although supporting data are limited. This study investigates distribution, concentration, and potential drivers of Fe-binding ligands in Antarctic sea ice, considering the ice type, location and season. Results suggest that the concentration of ligands (C L ) varies throughout the year, both spatially and seasonally. The lowest C L (3.3–8.0 nM) and DFe concentrations (0.7–3.5 nM) were recorded in newly formed winter sea ice in the Weddell Sea, likely due to the early stage of sea-ice growth and low biological activity. The highest C L (1.7–74.6 nM), which follows the distribution of DFe (1.0–75.5 nM), was observed during springtime, in the Eastern Antarctic Sector. There, consistently higher values for C L in bottom ice depths were likely associated with enhanced algal biomass, while aeolian deposition may have acted as an additional source of DFe and ligands near Davis station. In summer, the senescence of ice algae and advanced sea-ice melting led to intermediate C L (1.0–21.9 nM) and DFe concentrations (0.6–13.3 nM) both on and off the East Antarctic coast. Regardless of time and location, >99% of DFe was complexed, suggesting that C L controls the distribution of DFe in sea ice. This study represents a first attempt at a year-round investigation of C L in sea ice, providing results that support the premise that sea ice acts as a potential biogeochemical bridge between autumn and spring phytoplankton blooms.